2008
DOI: 10.1002/masy.200851101
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Nascent Polymerisation of Olefins on Supported Catalysts

Abstract: Summary: An improved gas phase reactor system has been designed and tested in order to study heat transfer in gas phase olefin polymerisation on supported catalysts. It is shown that temperature rise in a fixed bed configuration is highly dependent on the flow rate of gas, with higher outlet gas temperatures being observed at higher flow rates. In addition it is shown that the shape of the rate curve is dependent on the initial conditions of the reaction, suggesting that the mechanism of particle fragmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…11,29,30 In these previous studies, triethylaluminium (TEA)-treated silica was used as the inert diluent. This implies that solid liquid extraction is necessary to recover the polymer for analysis.…”
Section: Inert Seedbedmentioning
confidence: 99%
See 1 more Smart Citation
“…11,29,30 In these previous studies, triethylaluminium (TEA)-treated silica was used as the inert diluent. This implies that solid liquid extraction is necessary to recover the polymer for analysis.…”
Section: Inert Seedbedmentioning
confidence: 99%
“…29 Using this reactor, it was shown that it is possible to develop a relationship between how the heat transfer rate is controlled (governed mainly by gas flow rate) and the start-up kinetics of the polymerization of ethylene on a supported metallocene catalyst. It has also been used to show how a variation in the gas phase thermal conductivity can alter consistently the temperature profiles in the reactor thus giving very different values of catalyst activity.…”
Section: Introductionmentioning
confidence: 99%
“…40 ms) performed with a quenched-flow apparatus. More recently, Olalla et al [25] improved the original gas-phase short-stop technique [5,26] in order to study heat transfer in gas-phase olefin polymerization on supported catalyst; they found that the rate of reaction has a very strong influence on the rate of fragmentation and also showed that the shape of the rate curve is dependent on the initial conditions of the polymerization, suggesting that the mechanism of fragmentation of the catalyst carrier depends on the start-up of the polymerization. The latter observation confirmed an earlier result of Knocke et al [27] These and other articles in a similar vein all point to the fact that fragmentation influences the morphology, but that the rate of polymerization during the fragmentation step and the physical properties of the polymer present during this stage all interact in a complex manner.…”
Section: Introductionmentioning
confidence: 97%
“…Esta técnica permite o acompanhamento simultâneo do crescimento da partícula polimérica e da cinética de polimerização em polimerizações em fase gasosa. Pater et al [82,83] descreveram um Recentemente, Ollala et al [110] e Tioni et al [111] usaram o SSR [105] para estudar o mecanismo de transferência de calor em polimerizações de eteno em fase gasosa, conduzidas com catalisadores heterogêneos. De acordo com os autores, a taxa de polimerização exerce um forte efeito sobre a fragmentação, apresentando forte dependência com as condições iniciais da polimerização.…”
Section: Técnicas Experimentais Para Avaliação Da Fragmentação Catalíunclassified